2023
DOI: 10.3389/fpubh.2023.1072741
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors in Black female breast cancer survivors—Descriptive results from an online pilot study

Abstract: BackgroundBreast cancer (BC) research examining disparities in cancer survivorship and modifiable risk behaviors has been mostly cancer-specific, leaving relevant gaps in disparities research relating to other cancer survivorship outcomes, including cardiovascular disease (CVD). Maintaining healthy lifestyle behaviors is a critical component of successful cancer survivorship, where unhealthy behaviors may increase the risk for recurrence, second primary cancers, and incidence of new comorbid conditions, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous research has indicated that African Americans have a high prevalence of cardiovascular risk factors at the time of cancer diagnosis. For example, a study from the Maryland Cancer Registry found a 33% increase in the risk of cardiovascular mortality among African American women versus White women [ 100 ]. Fifty-one percent of the study’s survivors reported hypertension, and although only 7% were obese when they were initially diagnosed with breast cancer, 54% were obese when they were surveyed a few years after their initial diagnosis.…”
Section: Factors That May Contribute To Disparities In Anthracycline-...mentioning
confidence: 99%
“…Previous research has indicated that African Americans have a high prevalence of cardiovascular risk factors at the time of cancer diagnosis. For example, a study from the Maryland Cancer Registry found a 33% increase in the risk of cardiovascular mortality among African American women versus White women [ 100 ]. Fifty-one percent of the study’s survivors reported hypertension, and although only 7% were obese when they were initially diagnosed with breast cancer, 54% were obese when they were surveyed a few years after their initial diagnosis.…”
Section: Factors That May Contribute To Disparities In Anthracycline-...mentioning
confidence: 99%